INVESTIGATION OF CHALLENGES AND ADVANTAGES IN IMPLEMENTING ROBO JUSTICE AND AI- CASE STUDY ABOUT LEGAL SYSTEMS IN ITALY AND UZBEKISTAN - Khalikov Mukhriddin Sadulla Ogli (Western European Studies, 2024)
Thesis is associated with the introductory scenario of this research which is focused on the challenges and benefits of AI and robot justice practices in legal companies. The aim of this research along with objectives has been mentioned that is to identify the challenges in the process of implementation of AI and Robo-justice about legal system in Uzbekistan ad Italy. A critical discussion of research has been designed which is also highlighting the significant chances of this study
Keywords: extensive; designed; introductory; focused